High temperature superconductivity: puzzles & promises - Shaari, Abdul Halim (2004)

(untitled)
The discovery of high temperature superconductivity (HTS) in the non-inter-metallic compounds La2-x Bax CuO4 at 35 k(1986) and YBa2CuO37 at 93 K (1987) has been ranked as one of the most exciting advancement in modern physics, with profound implications for technologies. Superconductivity is perhaps the most remarkable phenomenon that has been bestowed to mankind. Historically, superconductivity appeared only in metals and alloys, termed as low temperature or conventional superconductors, and only near liquid helium temperatures (~4 TO 30 K), but within the past 16 years a very large family of superconductors have appeared in rather complex metallic cuprates, most of which are superconducting above liquid nitrogen temperatures (700 to 150 K). This discovery has raised hope that a wide range of applications would soon become a reality.